Kehadiran Ayah Maupun Nenek di Rumah Tidak Dapat Membantu Pemberian ASI Eksklusif di Indonesia - Etania Ranu Andhika (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
Exclusive breastfeeding (EBF) for the first six months is the key to preventing malnutrition in children. However, EBF coverage in Indonesia is only 38%, while the target WHO set in 2030 is 70%. Therefore, targeting the actors behind EBF completeness is needed to boost the EBF rate. The research will uncover the impact of the daily sources of support (both maternal and paternal grandmothers, the father, and the domestic worker) and modifying factors on the EBF choices made by the mother. Using the 2019 and 2020 National Socio-Economic Survey (SUSENAS) data, probit regression suggests that no one's cohabitation with the mother significantly affects EBF completeness. In contrast, maternal characteristics (employment status, economic level, education completion, and residential area of living), baby’s gender, and father’s education become the most decisive factors. Since the leading actor is still the mother herself, to improve the EBF rate, the policy should be focused on helping breastfeeding mothers to face the challenges, especially in the workplace.